Comparative study of the radiobiological effects induced on adherent vs suspended cells by BNCT, neutrons and gamma rays treatments - Cansolino, L. (2015)
The present work is part of a preclinical in vitro study to assess the efficacy of BNCT applied to liver or lung coloncarcinoma metastases and to limb osteosarcoma. Adherent growing cell lines can be irradiated as adherent to the culture flasks or as cell suspensions, differences in radio-sensitivity of the two modalities of radiation exposure have been investigated. Dose related cell survival and cell cycle perturbation results evidenced that the radiosensitivity of adherent cells is higher than that of the suspended ones.